Premature Aging Among Trauma Survivors—The Longitudinal Implications of Sleep Disruptions on Telomere Length and Cognitive Performance. (1st June 2019) - Aloni, Roy; Levin, Yafit; Uziel, Orit; Solomon, Zahava
Abstract: Objectives: Sleep is necessary for brain function as well as physical and cognitive processes. Sleep disruptions, common with aging, intensify among trauma survivors. Moreover, former prisoners-of-war (ex-POWs) often experience premature aging. This study investigates the longitudinal effects of sleep disruptions for ex-POWs in relation to cognitive performance and telomere length as well as between cognition and telomeres. Method: This study included Israeli veterans from the 1973 Yom Kippur War who participated in four assessments (1991, 2003, 2008, 2015): (a) ex-POWs ( n = 99), and (b) veterans who not were captured (controls) ( n = 101 ). Among both groups, sleep disruptions were assessed using a self-report item in all four assessments. Cognitive performance was assessed using the Montreal Cognitive Assessment (MOCA) and telomere length was assessed via total white blood cells (leukocytes) from whole blood samples using Southern blot, both were measured only among ex-POWs in 2015. We conducted descriptive statistics, repeated measures, correlations, and path analyses. Results: Sleep disruptions were related to lower cognitive performance but not to shorter telomeres. Moreover, cognitive performance and telomere length were found to be related when sleep disruptions were taken into consideration. Conclusion: Interpersonal trauma was shown to be a unique experience resulting in sleep disruptions over time, leading to cognitive impairment. These findings highlight the importance of viewing trauma survivors at high-risk for sleep disruptions. Therefore, it is imperative to inquire about sleep and diagnose cognitive disorders to help identify and treat premature aging.